2015
DOI: 10.3892/etm.2015.2800
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mutations of MDR3 exons 9 and 23 in infants with parenteral nutrition-associated cholestasis

Abstract: Abstract. The aim of this study was to investigate mutations of multidrug resistance 3 (MDR3) exons 9 and 23 in infants with parenteral nutrition-associated cholestasis (PNAC). A total of 41 infants with PNAC were enrolled in the study. Genomic DNA was extracted from the peripheral venous blood leukocytes of each patient and MDR3 exons 9 and 23 were amplified by polymerase chain reaction. One patient was identified who carried a frameshift mutation in MDR3 exon 23 (C.2793) that was caused by the insertion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Total parenteral nutrition is used to treat infants with gastrointestinal abnormalities, short bowel syndrome, malnutrition, inflammatory bowel disease, and idiopathic diarrhea. Parenteral nutrition-associated cholestasis is associated with mutations in ABCB4 (MDR3) in preterm infants (142). UDCA can be used as bile acid replacement therapy to improve lipid absorption in patients with parenteral nutrition-associated cholestasis.…”
Section: Acquired Cholestasis-intrahepatic Cholestasis Of Pregnancy (Icp) Affects ~1%mentioning
confidence: 99%
“…Total parenteral nutrition is used to treat infants with gastrointestinal abnormalities, short bowel syndrome, malnutrition, inflammatory bowel disease, and idiopathic diarrhea. Parenteral nutrition-associated cholestasis is associated with mutations in ABCB4 (MDR3) in preterm infants (142). UDCA can be used as bile acid replacement therapy to improve lipid absorption in patients with parenteral nutrition-associated cholestasis.…”
Section: Acquired Cholestasis-intrahepatic Cholestasis Of Pregnancy (Icp) Affects ~1%mentioning
confidence: 99%
“…Most cases improve on withdrawing the drug and adding UDCA. Recent studies have demonstrated, that ABCB4 mutations (c.504C>T and c.485T>Ain exon 6 and c.2793 frameshift mutation in exon 23) are possibly involved in the development of parenteral nutrition-associated liver disease in premature infants[ 36 ].…”
Section: Mdr3 Deficiencymentioning
confidence: 99%